2014
DOI: 10.4181/rnc.2013.21.852.6p
|View full text |Cite
|
Sign up to set email alerts
|

Terapia de Restrição e Indução ao Movimento no Membro Superior Parético Crônico – Relato de Caso

Abstract: Introdução. A Terapia de Restrição e Indução ao movimento (TRIM) consiste na imobilização do membro superior não parético, associado a um treinamento intenso do membro superior parético. Objetivo. O objetivo deste estudo foi verificar o efeito da TRIM na reeducação funcional do membro superior parético após Acidente Vascular Cerebral (AVC) com 11 anos de lesão. Método. Trata-se de um estudo de caso onde foi selecionada uma paciente com sequelas de hemiparesia espástica a direita e afasia motora decorrente do A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…Although this study presents a reduced sample size, it does not differ from other studies using mCIMT, since most are characterized as "case study" [5,13]. However, there is a general agreement that CIMT enables increase in dexterity and grip strength, improvement in functional independence, reduced average time to perform motor tasks [13,14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this study presents a reduced sample size, it does not differ from other studies using mCIMT, since most are characterized as "case study" [5,13]. However, there is a general agreement that CIMT enables increase in dexterity and grip strength, improvement in functional independence, reduced average time to perform motor tasks [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the best time to start the rehabilitation is the early phase of the disease, which corresponds to the first three months after injury, so as to the functional improvement is more evident at this time and the recovered motor function may persist due to neural plasticity. Nevertheless, it is known that in the chronic phase of stroke (six months after) neurological damages are identified more accurately, since there are compensatory movements and incorrect relearning or not acquiring of functions, impairing the functionality [5]. In addition, animal studies have shown that an overload of stimuli on the paretic limb, as occurs during treatment using mCIMT, in early stages after injury (up to 3 months), may be detrimental to recovery, as it may stimulate the mechanism of excitotoxicity, widening the area of the lesion [6].…”
Section: Introductionmentioning
confidence: 99%
“…Rodrigues et al 22 . destacam que a terapia por meio da TCI foi eficaz na funcionalidade de pacientes com lesão crônica, onde se observou ganhos, mensurados pelos graus da ADM na grande maioria dos movimentos, permanecendo o mesmo apenas nos movimentos de adução do ombro.…”
Section: Materials E Métodounclassified
“…destacam que a terapia por meio da TCI foi eficaz na funcionalidade de pacientes com lesão crônica, onde se observou ganhos, mensurados pelos graus da ADM na grande maioria dos movimentos, permanecendo o mesmo apenas nos movimentos de adução do ombro. Foi utilizada a goniometria para mensurar os resultados pré e pós-treinamento e os resultados apresentados obtiveram uma diferença estatisticamente significante entre as médias do antes e depois, após a utilização da TCI 22 . A Terapia de Contensão Induzida permite a eficácia do tratamento de disfunções motoras relacionadas à mobilidade do membro superior afetado pelo AVE, permitindo a percepção e utilização do membro nas atividades de vida diárias de modo eficaz quando comparado ao meio de terapia convencional 23 .…”
Section: Materials E Métodounclassified